Collaborative business process discovery: method and case study - Martins, Paula Ventura (2013)
Information flows across the organization are complex and procedures employed to understand, share and control organizational knowledge and experiences should be properly supported by collaborative environments. Nevertheless, few collaborative methodologies had been proposed to describe and evolve business processes. Existing tools don’t provide the right methods for business processes discovery, modeling, monitoring and improvement. In the future, business processes models should be the result of cross-team and cross-departmental collaboration, with involved business people sharing their personal knowledge and formalizing it. This paper focuses on case study applying a collaborative process discovery method. Business Alignment Methodology (BAM) is a methodology that provides guidance about how organizational practices and knowledge are gathered to contribute for business process improvement against current BPM approaches.